The lingo of travel: Understanding the motivating factors in language tourism - Christodoulou, Zoe (2019)
The purpose of this paper is to explore, using the Push-Pull framework, those forces which ‘push’ people to participate in language courses abroad as well as those elements which ‘pull’ them to choose a specific destination and language school. This paper uses an interpretive, qualitative approach, based on 15 in-depth interviews conducted with tourists who participated in language courses at schools in Italy and Spain. It was found that, besides a desire to learn or improve the language itself, tourists participate in language tourism to achieve self-determination and fulfil European identity-related goals. As a result, tourists are attracted to those destinations and language schools they feel will help them achieve autonomy, relatedness and competency as well as those which they perceive to be authentic. Nevertheless, this desire for self-determination and authenticity is contrasted in an interesting paradox, whereby participation in language tourism allows these tourists to satisfy their travel ‘itch’ without straying too far from the comfort zone. The findings can be represented in the sentence: ‘Give me a European identity, authenticity and control, but also give me the comfort of familiarity!’. A qualitative research design using in-depth interviews has not been previously applied to the study of language tourism motivation. In comparison to previous studies in educational tourism which have largely focused on students participating in International Exchange Programmes, the present study focuses on individuals who have chosen to study a language abroad outside of home-university affiliations. The main contribution of this paper is the discovery that the desire to travel abroad for language tourism emerges from a specific life context, the most interesting of which is the finding that the isolating politics of Brexit and Trump are pushing these tourists to seek a more European identity. These contexts are added to the push-pull framework to present a new theoretical model. The findings provide useful insights for marketing managers at language schools and destination management organisations to refine their offerings and appropriately design their marketing communications.